Learn Japanese words (Foreign language basics, ,, 2015)
"Learn fun and useful words and phrases in Japanese."--Publisher's website.

Learn Spanish words (Foreign language basics, ,, 2015)
Learn fun and useful words and phrases in Spanish.

Learn Mandarin Chinese words (Foreign language basics, ,, 2015)
Learn fun and useful words and phrases in Mandarin Chinese.

Learn Russian words (Foreign language basics, ,, 2015)
Provides useful words, numbers, greetings, and phrases in Russian. Additional features to aid comprehension include a table of contents, an introduction to the basic grammatical rules of the language, and an introduction to the author and illustrator. Learn fun and useful words and phrases in different languages! Each book in the Foreign Language Basics series includes words and phrases in a language other than English, as well as the English translations and pronunciation help. Each book also offers an introduction to facts and history about the language, and provides basic grammatical rules. Additional features to aid comprehension include a table of contents and an introduction to the author and illustrator.

Learn German words (Foreign language basics, ,, 2015)
Provides useful words, numbers, greetings, and phrases in German. Additional features to aid comprehension include a table of contents, an introduction to the basic grammatical rules of the language, and an introduction to the author and illustrator. Learn fun and useful words and phrases in different languages! Each book in the Foreign Language Basics series includes words and phrases in a language other than English, as well as the English translations and pronunciation help. Each book also offers an introduction to facts and history about the language, and provides basic grammatical rules. Additional features to aid comprehension include a table of contents and an introduction to the author and illustrator.

Learn French words (Foreign language basics, ,, 2015)
Learn fun and useful words and phrases in French.

Learn Arabic words (Foreign language basics, ,, 2020)
Provides useful words, numbers, greetings, and phrases in Arabic. Additional features to aid comprehension include a table of contents, an introduction to the basic grammatical rules of the language, and an introduction to the author and illustrator.
Introduction to Arabic , My home , In the morning , At school , At the park , Around town , In the store , My birthday party , Time for dinner , At night , More useful words.